Visual flow-through column biomimetic immunoassay using molecularly imprinted polymer as artificial antibody for rapid detection of clenbuterol in water sample. Issue 6 (2nd November 2017) - Tang, Yiwei; Zhang, Yuchen; Zhang, Hong; Liu, Xiuying; Gao, Xue; Lv, Changxin; Ma, Tao; Lu, Xiaonan; Li, Jianrong
ABSTRACT: A novel visual flow-through column biomimetic immunoassay using horseradish peroxidase-labeled clenbuterol (HRP-CLB) as a tracer and molecularly imprinted polymers (MIPs) with high specificity as the artificial antibody has been developed for rapid detection of CLB. Different intensities of blue color products on test layer of the column could be observed after reaction. This optimized assay provided a preliminary qualitative result in the concentration range of 0 to 1000 μg/L by judging color density of the test layer without any equipment, and the detection could be finished within 15 min. This assay was evaluated using CLB spiked water samples and results were comparable to high performance liquid chromatography method. The visual detection limit of 5 μg/L in water sample was obtained. This developed flow-through column biomimetic immunoassay was demonstrated as a suitable tool for rapid, sensitive, low-cost, and qualitative determination of CLB residues on site.